Temporal dynamics of neonatal hypoxic–ischemic encephalopathy injuries on magnetic resonance imaging - Holly Flyger; Samantha J. Holdsworth; Alistair J. Gunn; Laura Bennet; Hamid Abbasi (Neural Regeneration Research, 2025)
Moderate to severe perinatal hypoxic–ischemic encephalopathy occurs in ~1 to 3/1000 live births in high-income countries and is associated with a significant risk of death or neurodevelopmental disability. Detailed assessment is important to help identify high-risk infants, to help families, and to support appropriate interventions. A wide range of monitoring tools is available to assess changes over time, including urine and blood biomarkers, neurological examination, and electroencephalography. At present, magnetic resonance imaging is unique as although it is expensive and not suited to monitoring the early evolution of hypoxic–ischemic encephalopathy by a week of life it can provide direct insight into the anatomical changes in the brain after hypoxic–ischemic encephalopathy and so offers strong prognostic information on the long-term outcome after hypoxic–ischemic encephalopathy. This review investigated the temporal dynamics of neonatal hypoxic-ischemic encephalopathy injuries, with a particular emphasis on exploring the correlation between the prognostic implications of magnetic resonance imaging scans in the first week of life and their relationship to long-term outcome prediction, particularly for infants treated with therapeutic hypothermia. A comprehensive literature search, from 2016 to 2024, identified 20 pertinent articles. This review highlights that while the optimal timing of magnetic resonance imaging scans is not clear, overall, it suggests that magnetic resonance imaging within the first week of life provides strong prognostic accuracy. Many challenges limit the timing consistency, particularly the need for intensive care and clinical monitoring. Conversely, although most reports examined the prognostic value of scans taken between 4 and 10 days after birth, there is evidence from small numbers of cases that, at times, brain injury may continue to evolve for weeks after birth. This suggests that in the future it will be important to explore a wider range of times after hypoxic–ischemic encephalopathy to fully understand the optimal timing for predicting long-term outcomes.